Paradoxical pupil responses to isolated M-cone increments - Murray, Ian J.; Kremers, Jan; Mckeefry, Declan; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
M-cone onsets appear dimmer than the background and elicit electroretinograms (ERGs) resembling the light offset response. We sought a corresponding anomalous pupillary light reflex (PLR) using a 4-primary ganzfeld as stimulator and pupillometer. Increments and decrements of white light were compared with M- and L-cone onsets and offsets using silent substitution. Luminance bias (LB) could be added to or subtracted from the cone-isolating stimuli. There was a normal PLR to L-cone increments, but the pupil constricted mainly to M-cone decrements. Changing LB produced a neutral point where on and off responses were balanced. The results reflect ERG and psychophysical studies. This observation may be linked to the antagonistic nature of the M-cone input to cone opponent mechanisms.
EVALuna2:34924